Conceptualising de-radicalisation and former combatant re-integration in Nigeria. Issue 11 (2nd November 2018) - Clubb, Gordon; Tapley, Marina
Abstract: Nigeria has recently joined the many states which have established de-radicalisation programmes. The article engages with debates on how the success of de-radicalisation can be ascertained given the substantial flaws of using individual-oriented recidivism rates as a measure. Many studies on de-radicalisation emphasise the need to consider the programme's context to facilitate success, yet 'context' has been under-conceptualised and approached statically. The paper provides greater agency to 'the context' in distinguishing between the type of milieus former combatants are re-integrated into and how these emergent social relations shape the scope of de-radicalisation programmes, beyond the traditional over-emphasis on programme participant outcomes as measures of success. The Nigerian de-radicalisation programme has a broader function insofar as it provides former combatants with 'scripts' of disengagement and function as a brand, signalling to communities that former combatants have repented and are 'better citizens, imbued with genuine nationalism' that resonate with local communities.